Patients' observations of bioprosthetic valve failure: "my heart is honking, doctor". Issue 6 (December 1990) - Errington, M; Bloomfield, P; Starkey, I R; Shaw, T R
Abstract : Audible cardiac murmurs are uncommon and may indicate severe native valve dysfunction. In six patients with bioprosthetic mitral valves audible honking systolic murmurs suddenly developed. Doppler echocardiography showed characteristic striated regurgitant signals. At operation each prosthesis had torn cusps. New audible murmurs and striated Doppler signals originating from mitral bioprosthetic valves are indicators of cusp tears. Recognition of this is important because early detection of prosthetic valve dysfunction may improve subsequent surgical outcome.